2018
DOI: 10.1016/j.aej.2017.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-hydraulic analysis of VVER-1000 residual heat removal system using RELAP5 code, an evaluation at the boundary of reactor repair mode

Abstract: Removing the residual heat from a nuclear reactor is an important safety aspect of thermal hydraulic analysis. In this study, a typical VVER-1000 reactor residual heat removal system has been evaluated using RELAP5 thermal hydraulic loop code during cool-down. Reactor cooling down starts from hot state temperature and then continues to the cool-down stages with 130°C and 70°C, respectively. The second stage of cooling down is the boundary of the reactor repair condition. Main cooling pump head, steam generator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The results showed that the inherent safety of secondary PRHRS is better, and the area of heat transfer and the vertical distance of cold and heat sources are the main factors affecting the system. Tabadar et al 13 used RELAP5 to evaluate the PRHRS of VVER‐1000, and the calculation results were consistent with experimental data and safety analysis reports. It was recommended that RELAP5 could be used to analyze VVER‐1000 during reactor cooling.…”
Section: Introductionmentioning
confidence: 55%
“…The results showed that the inherent safety of secondary PRHRS is better, and the area of heat transfer and the vertical distance of cold and heat sources are the main factors affecting the system. Tabadar et al 13 used RELAP5 to evaluate the PRHRS of VVER‐1000, and the calculation results were consistent with experimental data and safety analysis reports. It was recommended that RELAP5 could be used to analyze VVER‐1000 during reactor cooling.…”
Section: Introductionmentioning
confidence: 55%
“…For VVER-1000, s = 12.75 mm, and d = 9.1 mm [33]. k 3 accounts for the heated length effect and is analogous to Groeneveld's K 4 .…”
Section: Bobkov Look-up Tablementioning
confidence: 99%
“…The degree to which the assemblies used for constructing the LUT were "unbalanced" varied from 0.42 to 0.93 [8]; the value 0.93 corresponding to a bundle containing 37 rods. The number of fuel rods in a VVER-1000 assembly is 311 [33], so we can safely assume that k 5 = 1.…”
Section: Bobkov Look-up Tablementioning
confidence: 99%
“…For the VVER series, the VVER-1000/V412, V428M, and V528 are equipped with passive residual heat removal system (PRHRS) consisting of 4 trains with 33% capacity each, in which each train is connected into 1 horizontal steam generator. The steam line of steam generator has a bypass line into the finned tube air heat exchangers, which are used to reject core heat to the outside atmosphere [18,19,20]. There are 4 HXs for each train inside a chimney-like structure along the outer surface of containment up to the top of the containment to enable a natural circulation of air as shown in Figure 5.…”
Section: Engineered Safety Features In Case Of Sbomentioning
confidence: 99%